Thermal Loading of the Railway Wheel during Downhill Breaking - Juraj Gerlici; Peter Vesely; Tomas Lack (Communications - Scientific letters of the University of Zilina, 2001)
The paper deals with the particular factors of railway wheels heat loading while braking with a brake block and consequences of that stressing. There are discussed some phenomena of thermic interaction between the bracked wheel and the brake block. The attention is aimed to the rising and spreading of thermic fields into a wheel and brake block too. Next, there are pointed out the manner and possibilities of solution of nonstationary thermal field course. Considering the difficulty of an analytical solution the emphasis is given to the results of the experimental works on the brake bench. A compendium of the particular design variants of the monoblock railway wheels and the assessment of their suitability from the point of view of stress and deformation creates the individual chapter.